Práticas integrativas e complementares: os desafios da institucionalização em um município mineiro - Ribeiro, Eveline Massa (2017)
This paper aims to analyze the process of institutionalization of Integrative and Complementary Practices (PICs) in the city of Belo Horizonte, as a case study to understand the challenges and facilitators of the implementation process in municipalities. The theoretical composition brings the debate between the biomedical model and the integral health model advocated by the PICs, the influence of the Brazilian Health Reform and global and national health conferences, the creation of the SUS, primary health care and how this affects current policies implementation of PICs, especially the National Policy of Integrative and Complementary Practices (PNPIC). Other studies on the performance of PICs in other Brazilian municipalities are also highlighted. As a methodology was used the analysis of public policies of Baptista (2011), analyzing semi-structured interview of managers and executor health professionals of the three programs operating in Belo Horizonte. It was observed from the interviews analysis that a municipal policy of PICs is important to guide the programs, awareness of health professionals for referrals and collaboration, information and dissemination about the practices to the community, the use of a data system to quantify the impacts of the programs in the life quality of the population, the necessity of valorization of the practices in relation to the biomedical model. These scores are common to all three programs, while each of them also has specific questions. It is hoped that the collection of these data will help in understanding the institutionalization of PICs and their impacts on the health of the population.